Information System for Operational Goods Management at the Career Guidance and Entrepreneurship Center Malikussaleh University - Rizki Suwanda; Said Fadlan Anshari; Wardina Ningsih (LPPM Politeknik Aceh Selatan, 2024)
Managing operational goods manually leads to slow and inefficient work performance, hence the design and implementation of an information system that can efficiently manage operational goods needs to be done in a structured manner and work optimally. Analysis of operational goods needs is conducted through observation and interviews with relevant parties to discuss the problems faced and identify the required features. Some key features implemented in this system include complaint management for operational goods needs, which can be managed and utilized for effective procurement or requests for goods according to requirements. This system is designed using the PHP programming language with the Codeigniter framework and MySQL database for database management. With this system in place, it is expected to assist in the more effective and systematic management of operational goods needs at the Career Guidance and Entrepreneurship Center of Malikussaleh University.